Letter to Jane Tolmach from James C. Basile - James C. Basile:::::: (1962)
A letter from James C. Basile of the California Democratic Council argues that all members of CDC-affiliated clubs are required by the organization's constitution to support only Democratic candidates for public office. He disputes the claim that this rule applies only to officers and directors, citing Article IV on membership to support his interpretation. Basile defends the Ventura County Democratic Council's decision to expel members who supported Republican candidates in partisan races. He contends that party unity and electoral success depend on loyalty to Democratic nominees, even if some members are unenthusiastic about specific candidates. He concludes that Democratic organizations cannot tolerate members who defect to support Republicans.